Empowering Afghan Refugee Youth through Market-Oriented Hospitality Trades: Pathways to Sustainable Employment and Repatriation Integration in Pakistan and Afghanistan - Muhammad Yaqub; Nafeesa Mir Zaman; Salman Khan (Dialogue Social Science Review (DSSR), 2024)
This is a big challenge for Afghanistan and Pakistan as millions of refugee people are suffering from a very difficult life due to displacement, limited educational facilities for children and no proper employment opportunities. However, market-oriented training in disciplines such as hotel and tourism industries, plumbing, electrical installation, or carpentry for Afghan refugee youth not only deal with the current problem but also open up opportunities for a sustainable solution for youth refugee integration into the Pakistani society and for successful repatriation in productive areas in Afghanistan. In this regard, by using qualitative research methodology, the possibility of skill development programmes which can help address the increase in demand or qualified workforce in both Foreign as well as home countries is studied access to education, and lack of viable livelihood opportunities. Based on the hospitality and skilled trades areas of this study due to the excellent employability rates the lack of training for Afghan refugee youth in the future is recommended. The study offers essential information to the governments, NGOs, and local companies to understand the strategies to respond to Afghan youth’s employability, career, and socio-economic reintegration needs for productive work. The purpose of this study is to develop and execute a market-led professional training program for Afghan refugees male and female with the Pakistan and Afghanistan desired skilled trade areas in the hospitality industry.